Students who do not play at home have lower self-esteem: results of the multicenter study Active Classes Chile - Maria Alejandra Valencia-Pacheco; Daniel Reyes-Molina; Alejandra Robles-Campos; Igor Cigarroa; Yasna Chávez-Castillo; Isidora Zañartu; Mairena Sánchez-López; Sonia Sepúlveda-Martin; Marcela Núñez Solís; Tomas Reyes-Amigo; Jessica Ibarra-Mora; Juan de Dios Benítez-Sillero; et al. (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: The association between physical activity for health and socio-emotional well-being in children and adolescents is widely documented. However, the relationship between active play and self-esteem in schoolchildren is unknown, especially when considering sociodemographic variables that influence active play.